Assessment of genetic diversity in sesame (Sesamum indicum L.) detected by Amplified Fragment Length Polymorphism markers - Ali, Ghulam Muhammad; Yasumoto, Sirato; Seki-Katsuta, Masumi (Electronic Journal of Biotechnology, 2007)
Sesame (Sesamum indicum L.) is one of the oldest oil crops and is widely cultivated in Asia and Africa. To determine the level of genetic diversity in relation to geographical origins and morphological characteristics, a total of 96 accessions have been collected from different parts of the world and were analyzed using AFLP techniques. Twenty-one primer pairs generated a total of 445 bands and among them 157 (35%) were polymorphic. Using UPGMA clustering analysis method based on the similarity coefficient, accessions were separated into two major groups. The first group mostly consists of Eastern Asian origin and another group consists of South Asian origin. Sub-clusters separated the accessions and form distinct diversity among groups. Considering the relatednessof accessions, geographical origin and their morphological characteristics are reflected to the similarity of AFLP pattern.